1999
DOI: 10.1046/j.1523-1755.1999.07138.x
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat diet aggravates tubulointerstitial but not glomerular lesions in obese Zucker rats

Abstract: A high-fat diet aggravates tubulointerstitial but not glomerular density lipoprotein (LDL) [1]. Although many studies lesions in obese Zucker rats.have evaluated the effects of dietary fat on glomerular Background. Despite a large body of evidence that manipulesions, limited information is available regarding its eflation of dietary fat alters glomerular lesions, reports regarding fects on tubulointerstitial lesions. To examine whether a the effects of dietary fat on tubulointerstitial lesions are limited. hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…1). This observation is consistent with the findings of a previous study using male lean Zucker rats, in which a less pronounced high-fat diet (20% of calories derived from fat) was provided over 30 wk (30). However, it is clear that the proportion of consumed calories derived from fat was markedly higher in the HFF group (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1). This observation is consistent with the findings of a previous study using male lean Zucker rats, in which a less pronounced high-fat diet (20% of calories derived from fat) was provided over 30 wk (30). However, it is clear that the proportion of consumed calories derived from fat was markedly higher in the HFF group (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Matsuda et al (30) fed male lean Zucker rats a 20% fat diet for 30 wk and reported a greater body weight gain, increased plasma triglycerides, and enhanced plasma thiobarbituric acid-reacting substrates, an index of oxidative stress. Maher et al (28) fed male lean Zucker rats a 48% fat diet for 6 wk and observed an enhanced body weight gain, but no effects on plasma glucose or insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, the widening of the mesangial area occurred, and led eventually to renal failure, the main cause of increased mortality recorded in hamsters fed with saturated-fat diets. Our data corroborate and extend the findings of previous studies showing that obesity and high-fat diets are linked with kidney dysfunction in rats [6,8] and dogs [12]. The exact mechanism of this has not been defined but could involve input from non-esterified fatty acids [39].…”
Section: Discussionsupporting
confidence: 92%
“…Lipids have been shown to induce glomerular expression of chemoattractants such as MCP-1, monocyte-colony-stimulating factor (M-CSF), migration inhibitory factor (MIF), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) [47][48][49] and various animal models of hyperlipidemia-induced renal disease have demonstrated increased influx of macrophages into glomeruli [28,30,34,50] and into the tubulointerstitium [23,29,51,52] of affected animals. The functional importance of macrophages in mediating renal injury in hyperlipidemic states is highlighted by work done by Pesek-Diamond et al [51] showing that depletion of macrophages resulted in an amelioration of renal function impairment and reduction of glomerulosclerosis and matrix expansion in hyperlipidemic rats with acute puromycin aminonucleoside nephrosis.…”
Section: Discussionmentioning
confidence: 99%